Advances in biosensors for medical diagnostics - SHASHI SURI (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Biosensors are analytical devices that combine biological recognition elements with physicochemical transducers. This paper will discuss recent advancements in biosensor technology for medical diagnostics, focusing on their applications in disease detection and monitoring.